Repression of a herpes simplex virus immediate-early promoter by the Oct-2 transcription factor is dependent on an inhibitory region at the N terminus of the protein. - Lillycrop, K A (1994)
The B-cell form of the Oct-2 transcription factor Oct 2.1 can activate the herpes simplex virus immediate-early gene 3 (IE3) promoter, whereas the neuronally expressed Oct 2.4 and 2.5 forms of the protein, which contain a different C terminus, can repress this promoter. Here we show that partial or full deletion of the C terminus of Oct 2.1 in the presence of an intact N terminus results in a protein which can strongly repress the IE3 promoter. In contrast, deletion of the entire N terminus or a short region within it leaving the C terminus intact results in a very strong activator. Deletion of both N and C termini leaving only the isolated POU domain generates only a very weak repressor. The N-terminal region defined in this way can repress a heterologous promoter when linked to the DNA-binding domain of the GAL4 factor, indicating that it can function as an independent inhibitory domain. These results indicate that a specific region within the N terminus common to Oct 2.1, 2.4, and 2.5 plays a critical role in the ability of neuronally expressed forms of Oct-2 to repress the IE3 promoter but can do so only when the C-terminal region of Oct 2.1 is altered or deleted.